Integrasi Nilai Keislaman dalam Budidaya dan Pemasaran Tanaman Hias: Studi Kasus pada Ganda Nursery - Ratna Sari Dewi; Dea Ananda; Devia Pratiwi; Novi Aulia Safina; Vira Septria (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the cultivation process and marketing management strategies of ornamental plants applied by Ganda Nursery as one of the MSMEs in the horticulture sector. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that Ganda Nursery has succeeded in implementing sustainable ornamental plant cultivation techniques, including through the selection of superior seeds, the use of organic planting media, and pest control based on botanical pesticides. From a management aspect, Ganda Nursery utilizes digital marketing strategies through social media such as Instagram and WhatsApp to expand market reach and increase sales. This success cannot be separated from the application of sustainability principles and Islamic values ​​that emphasize the importance of managing natural resources wisely and responsibly. The obstacles faced include fluctuations in market demand, business competition, and limited resources, but are overcome by product innovation and improving service quality. This study is expected to be a reference for other MSMEs in developing sustainable and highly competitive ornamental plant businesses.